2007
DOI: 10.15666/aeer/0502_123138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plant Diversity and Prioritization of Communities for Conservation in Mornaula Reserve Forest

Abstract: Abstract. Assessment of plant diversity of the Reserve Forests of the west Himalaya and prioritization of communities for conservation have not been given much attention. Therefore, the study has been conducted in a biodiversity rich Mornaula Reserve Forest between 1500-2200m to analyse the structure, composition of the forest communities including richness of economically important, native, endemic and rare-endangered species, and prioritize communities for conservation. A total of 123 sites were sampled. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
(24 reference statements)
4
12
0
1
Order By: Relevance
“…These values of density are within the earlier values reported by various authors like Pant and Samant (2007);Semwal et al (2010), Gairola et al (2011);Raturi (2012) and Bhat (2012). Shrub density varied from 4,730±474 to 9,530±700 ind/ha.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These values of density are within the earlier values reported by various authors like Pant and Samant (2007);Semwal et al (2010), Gairola et al (2011);Raturi (2012) and Bhat (2012). Shrub density varied from 4,730±474 to 9,530±700 ind/ha.…”
Section: Discussionsupporting
confidence: 90%
“…Shrub density varied from 4,730±474 to 9,530±700 ind/ha. Pant and Samant (2007) reported shrub density ranging from 704 to 11,056/ha. Gairola et al (2011) reported shrub density ranging from 6639-24853/ha from different moist temperate forests of Garhwal Himalaya.…”
Section: Discussionmentioning
confidence: 99%
“…Kedarnath Wildlife Sanctuary (KWLS) was established in 1972 and is famous for the endangered Musk Deer. The KWLS is one of the largest protected areas (975 km 2 ) in the Western Himalaya located in ChamoliRudraprayag districts (25,293.70 ha in Chamoli district and 72,224.10 ha in Rudraprayag district) of Uttarakhand and falls under the IUCN management Category IV (Managed Nature Reserve) in the Biogeographical Province 2.38.12 of Himalayan highlands. The sanctuary lies in the upper catchment of the Alaknanda and Mandakini Rivers, which are major tributaries of Ganges.…”
Section: Study Areamentioning
confidence: 99%
“…This may affects diversity of woody plant species to the extinction and challenges sustainable management of resources in the forest coffee. The loss of biodiversity and the changing pattern of woody species have necessitated the assessment of woody species diversity (Pant & Samant, 2007;Tolera et al, 2008;Mebrat & Gashaw, 2013).…”
Section: Introductionmentioning
confidence: 99%